2017
DOI: 10.1021/acs.nanolett.7b00995
|View full text |Cite
|
Sign up to set email alerts
|

Bioresponsive Polyoxometalate Cluster for Redox-Activated Photoacoustic Imaging-Guided Photothermal Cancer Therapy

Abstract: Although various types of imaging agents have been developed for photoacoustic (PA) imaging, relatively few imaging agents exhibit high selectivity/sensitivity to the tumor microenvironment for on-demand PA imaging and therapy. Herein, molybdenum-based polyoxometalate (POM) clusters with the highest oxidation state of Mo(VI) (denoted as Ox-POM) were designed as novel agents for redox-activated PA imaging-guided photothermal therapy (PTT). Capable of escaping from recognition and capture by the liver and spleen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
118
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(122 citation statements)
references
References 44 publications
4
118
0
Order By: Relevance
“…Due to benefits such as reducing unnecessary biopsies and facilitating imaging‐guided cancer theranostics, noninvasive imaging has attracted considerable research interest . PA imaging is among the most promising biophotonic diagnostic modalities, in multiple ways superior to many other traditional optical imaging techniques .…”
Section: Methodsmentioning
confidence: 99%
“…Due to benefits such as reducing unnecessary biopsies and facilitating imaging‐guided cancer theranostics, noninvasive imaging has attracted considerable research interest . PA imaging is among the most promising biophotonic diagnostic modalities, in multiple ways superior to many other traditional optical imaging techniques .…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the upregulated glycolytic metabolism during tumorigenesis generates massive lactic acid, which results in an acidic TME with low pH value . Also, it has been demonstrated that the reductive property of tumor cytosol and the glutathione (GSH) content in tumor tissues are at least fourfold higher than that in normal tissues . In a word, the TME of solid tumor is distinctly featured with high content of GSH, H 2 O 2 , and H + .…”
Section: Introductionmentioning
confidence: 99%
“…Under laser irradiation, PSs for PTT can convert light energy into heat to implement local thermotherapy for killing cancer cells, while PSs for PDT can convert oxygen into reactive oxygen species (ROS) to kill tumor cells. Several types of inorganic nanomaterials have been explored for phototherapy, such as gold, carbon, and metal sulfides . Although superior efficiency in inhibiting tumor growth has been achieved, the potential long term toxicity of the inorganic nanoparticles cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%